2012
DOI: 10.1016/j.ultsonch.2012.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted extraction of geniposide from Gardenia jasminoides

Abstract: Fructus gardeniae (Zhizi), one of commonly-used traditional Chinese medicines, is derived from the ripe fruit of the evergreen shrub, Gardenia jasminoides Ellis, and is an ingredient of many traditional Chinese preparations, and has numerous pharmacological actions. Geniposide is the important bioactive element derived from F. gardeniae. This study established optimum conditions and method of ultrasound-assisted extraction for geniposide from F. gardeniae by exploring the different experimental parameters, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 21 publications
0
39
0
3
Order By: Relevance
“…3. There was a steady increase in the yield of pigment up to 38 min and it could be explained that, swelling and hydration of plant material could be accelerated by cavitation effect of the ultrasonic waves during the earlier period of extraction (Wang et al 2012). The asymmetric collapse of micro-bubbles near surfaces was also associated with microjets that could cause the disruption and good penetration of solvent (Vilkhu et al 2008) into the matrix (Sun and Tomkinson 2002) through diffusion which improves the washing out of pigment content from plant material to surrounding solvents and enhanced the extraction performance.…”
Section: Response Surface Analysismentioning
confidence: 99%
“…3. There was a steady increase in the yield of pigment up to 38 min and it could be explained that, swelling and hydration of plant material could be accelerated by cavitation effect of the ultrasonic waves during the earlier period of extraction (Wang et al 2012). The asymmetric collapse of micro-bubbles near surfaces was also associated with microjets that could cause the disruption and good penetration of solvent (Vilkhu et al 2008) into the matrix (Sun and Tomkinson 2002) through diffusion which improves the washing out of pigment content from plant material to surrounding solvents and enhanced the extraction performance.…”
Section: Response Surface Analysismentioning
confidence: 99%
“…Winter rapeseed cultivar specific surface areas and decrease yields of the extracted compounds (Wang et al 2012). For comparison, AhmadQasem et al (2013) observed that the increase in antioxidant capacity of the olive leaf extracts was almost negligible after 15 min of extraction, which indicates that continuous ultrasound application seems to have no effect on bioactive compounds.…”
Section: Spring Rapeseed Cultivarmentioning
confidence: 99%
“…This phenomenon could be explained due to the fact that ultrasound might induce acoustic cavitation and rupture of plant cells. The rupture of the bubbles will promote the interpenetration of the solvent into the plant cells to dissolve polysaccharides [25]. Prolonging extraction time resulted in a faintly increased yield of polysaccharides, indicating that the yield of polysaccharides started to maintain a dynamic equilibrium with increasing extraction time.…”
Section: Effect Of Extraction Time On the Yield Of Askpmentioning
confidence: 99%